MBBC CHAMPION TO COMPETE IN COPENHAGEN, DENMARK - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 20 March 2016 The “Malaysian Brain Bee Challenge (MBBC) 2016” is a project pioneered by the Neuroscience Department, School of Medical Sciences, Universiti Sains Malaysia (USM), Kubang Kerian with the cooperation of the Society for Neuroscience (Kelantan Chapter).